Challenges and Threats of the Digital Economy to the Sustainability of the National Banking System - M. N. Dudin; S. V. Shkodinsky (Финансы: теория и практика, 2022)
The goal of the study – development of specific methodical reasoned proposals on improvement of the mechanism for ensuring sustainable development of the national banking system and its security against external challenges and threats to cyberspace. The scientific novelty consists in a comprehensive analysis of the processes of ensuring the cyber stability of the Russian banking system in the context of escalation of external challenges and threats to the digital economy. The authors used the following methods: general scientific (observation, comparison, measurement, analysis and synthesis, logical reasoning method), specific scientific (static analysis, peer review, graphical method). In the article conducted a critical review of domestic and foreign scientific literature and practical recommendations to ensure the protection of the banking institution from cyber threats in the digital economy; presented a comparative analysis of the organization of the cybersecurity system in the Russian and foreign banking systems; done multidimensional statistical analysis of cyber threats for Russian banks; substantiated recommendations and proposals on organizational, economic and legal improvement of the system of protection of Russian banks from internal and external cyber threats. As a result, it is shown that the main problem points (zones) of the banking system, creating the prerequisites for the occurrence of cyber-risks are: 1) there is no exchange of information on cyber-attacks and their mechanisms; 2) banks interact inefficiently with the state regulator of Internet – Roskomnadzor; 3) low level of competence of bank employees who are responsible for cybersecurity; 4) limited budget of small and medium-sized banks that wouldn’t allow them to care independent cyber-protection units; 5) growing popularity of new fintech services and new fintech companies. The author draws a conclusion that the following measures are necessary for organizational, economic and legal improvement of the system of protection of Russian banks from internal and external cyber threats: the processes of development of banking ecosystems should be intensified; a federal interbank register of cyber fraudsters must be created; a single banking «polygon» for testing cyber threats needs to be developed.